PENGEMBANGAN E-MODUL PENUNTUN PRAKTIKUM KIMIA MATERI TITRASI ASAM BASA - Kurnia, Nina; Dewi Handayani; Elvinawati (ALOTROP, 2025)
This study aims to determine the feasibility, student responses, and students' psychomotor assessments when using the developed e-module for chemical practicum guidance on acid-base titration. The development of this e-module uses the ADDIE development model limited to the development stage. This study was conducted in class XII.MIPA C of SMA Negeri 2 Kota Bengkulu with 12 students as research subjects. The instruments used in this study were interview sheets, student needs questionnaires, expert validation sheets, student response questionnaires, and student psychomotor assessment sheets. Based on the results of the study, the results of the e-module feasibility test by expert validators were 91.2% with a very valid category. The results of the student response test on the e-module for chemical practicum obtained a percentage of 85.7% with a very good category, and the results of the student psychomotor assessment during the practicum using the e-module guidance obtained a percentage of 93% with a very good category. Keywords: E-Module; Development of Practical Guide; Acid-Base Titration